2007
DOI: 10.1111/j.1523-5378.2007.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection in Pediatrics

Abstract: During the last year, epidemiologic studies have shown that spontaneous clearance of Helicobacter pylori infection has a less significant role in countries with high prevalence and, in contrast to adults, there is no male predominance of H. pylori infection in children. Early acquisition of H. pylori may play a role in the development of recurrent abdominal pain in children less than 5 years of age. In this very young age group, the adequate performance of stool antigen test and (13)C urea-breath test demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 66 publications
0
6
0
3
Order By: Relevance
“…Our experience of the use of noninvasive tests confirms that of previous publications reporting the high sensitivity and specificity of UBT , whether employed before treatment to confirm or exclude infection or used to confirm HP eradication. In contrast, the sensitivity of SAIT in this study was very low and completely different from that reported in other studies .…”
Section: Discussionmentioning
confidence: 99%
“…Our experience of the use of noninvasive tests confirms that of previous publications reporting the high sensitivity and specificity of UBT , whether employed before treatment to confirm or exclude infection or used to confirm HP eradication. In contrast, the sensitivity of SAIT in this study was very low and completely different from that reported in other studies .…”
Section: Discussionmentioning
confidence: 99%
“…Çocukluk çağının, H. pylori enfeksiyonunun edinilmesinde önem-li bir dönemi oluşturduğu gösterilmiştir (4). Özellikle KKA olan çocuklarda %20'lerde H. pylori pozitifliği bildirilmiş olmakla birlikte, bu pozitifliğin hastalık gidişini etkilemediği saptanmıştır.…”
Section: Introductionunclassified
“…On one hand, this could result in enhancing the progression to cancer through premalignant lesions; while, on the other hand, cytokines may be responsible for better capabilities to clear H. pylori infection after acquiring the microorganism. There is evidence showing that a proportion of individuals spontaneously clear the infection [32]. In a pediatric study in Jamaica, it was found that the presence of the IL-1A-889 T allele was associated with a lower risk of H. pylori infection (with 43% risk reduction) [33].…”
Section: Host Geneticsmentioning
confidence: 99%